THE SAFETY FACTOR ANALYSIS OF THE MARINE SLOPE STABILITY MODEL ON THE ACCESS CHANNEL OF MARINE CENTRE PLAN CIREBON, WEST JAVA. - Franto Novico; Nur Adi Kristanto (BULLETIN OF THE MARINE GEOLOGY, 2010)
This study is focused on access channel model that safety factors of some slopes stability would be investigated. Plaxis version 8 is applied to analyze a magnitude of safety factors and displacements based on three different slopes of access channel there are 30°, 45° and 60°. Furthermore, parameters are adopted from geotechnical drilling and laboratory tests. A finite element is applied as a simple model to analyze within a Mohr-coulomb equation. Based on soil data analyses on Marine Center Plan, indicates low safety factor and high deformation. As results, 10 to 40 meters deformation of the slopes and 0.80 to 2.34 of safety factor are obtained of the models. For that reason, a combination between slope channel and infrastructure must be considered. Keywords: Safety factor, slope stability, access channel, Marine centre, Plaxis Kajian ini dilakukan terhadap faktor keamanan dari beberapa jenis kemiringan dinding alur pelayaran yang selanjutnya dilakukan pemodelan dengan menggunakan alur pelayaran Besarnya keruntuhan dan faktor keamanan pada beberapa sudut kemiringan yang berbeda telah dianalisis dengan menggunakan perangkat lunak geoteknik Plaxis Versi 8. Tiga jenis kemiringan yang berbeda telah dibuat yaitu sudut kemiringan 30°, 45° dan 60°. Sebagai data masukan, parameter diambil berdasarkan hasil pemboran geoteknik yang telah dianalisis di laboratorium. Model sederhana elemen terbatas telah dibuat dan dianalisis berdasarkan persamaan Mohr-Coulumb. Berdasarkan analisis data tanah pada rencana Marine Centre menunjukan faktor keamanan yang rendah dan deformasi yang besar. Total deformasi yang dihasilkan berkisar 10-40 meter dengan nilai faktor keamanan 0,80~2,34. Oleh karena itu, dari hasil tersebut perlu dipertimbangkan untuk mengkombinasikan kemiringan alur dengan infrastruktur. Kata kunci : faktor keamanan, kemiringan lereng, alur pelayaran, Marine centre, Plaxis